PHENETIC ANALYSIS OF POPULUS NIGRA, P. LAURIFOLIA AND P. × JRTYSCHENSIS IN NATURAL HYBRIDIZATION ZONE - A. V. Klimov; B. V. Proshkin (Вавиловский журнал генетики и селекции)
The wide spread of hybridization in the genus Populus, including spontaneous hybridization, caused by cultivars, requires studying the variability and inheritance of morphological traits by hybrids for initial tracking of these processes. The analysis of endogenous, intra- and inter-population variability was performed on 533 individual poplar trees in seven populations of P. nigra, seven populations of P. laurifolia and four populations of P. × jrtyschensis in the Tom river basin. On each specimen, 15 leaves from short mid-crown branches were collected to determine the shape of the leaf blade, the shape of its tip and base, as well as the branch morphotype. Some biometric indicators were proposed for geometric assessment of the leaf blade shapes of poplar species. The analysis showed that of all the traits examined only the leaf blade shape did not meet the criterion for “phene”, since it is usually represented by several forms in the crown of one and the same tree. In all the species studied, the level of their intra-population diversity was found to be much higher than the inter-population one. According to the increase of intra-population variability of qualitative traits, the taxa could be ranked as P. nigra < P. laurifolia < P. × jrtyschensis. The share of inter-population diversity differed among the species studied, accounting for 21.5% in P. laurifolia, 13.8% in P. nigra and 8.0% in P. × jrtyschensis. The P. laurifolia populations showed the greatest inter-population differentiation, most likely because of a disjunct distribution due to narrow specialization to the montane river environment. The lower differentiation in P. nigra is probably due to the facts that this species dominates the poplar stands of the Tom River basin; its populations are not fragmented and are linked by vast gene flow. In P. nigra, an increase in the diversity of qualitative characteristics and phenotypes was observed in populations confined to hybridization centers. Natural selection is most likely the factor governing the inter-population differentiation in P. × jrtyschensis, leading to the predominance of F1 hybrids in populations and hence to a sharp decrease in inter-population variability.